Applications of a geographic information system–based business intelligence system for decision making at Coffee Refresh. Issue 1 (10th April 2023) - Chaiprasert, Araya; Taweekarn, Naphat; Chongwatpol, Jongsawas
This case is designed to illustrate how to utilize a business intelligence framework and a geographic information system to make better decisions on franchise opening requests. The case started when Jong, the senior certified analytics professional, and his team were drafting a proposal presentation on a new franchise approval process to present to Tony, the director of Coffee Refresh. Currently, Coffee Refresh was experiencing a significant delay in approving franchise opening requests. In addition, the current approval process was relied on the appraisal teams' evaluations, which involved self-judgment as to the accessibility and visibility of the store location in each franchise opening request and a manual count of the potential targeted customers at each location, which impacted how the appraisal teams estimated the expected revenue for each location. During the first meeting with Jong and his team, Tony was frustrated by the current evaluation process, resulting in a significant backlog of requests pending approval, which was far behind the target for its franchise branch expansion strategy. It had also been reported that the branches that opened during the past few years had a relatively low success ratio (losses between 4.8% and 16.5%) and that the rate of branch closures had increased from 2% to 7.5%. Currently, eight franchise opening requests were pending, and Jong had to provide a recommendation for which requests should be approved. Coffee Refresh could approve all of them instantly, approve some of them, or even decline all of them. This was a great opportunity for Jong and his team to revisit the current franchise approval process and to demonstrate how business intelligence systems could improve the request approval process as well as address the issues of the current franchises' underperformance and the closure rates.